Reviews (Blackfriars, 1934)
theology and religion: The Unknown God. By Alfred Noyes. theology and religion: The Mystery of Stigmata from Catherine Emmerich to Teresa Neumann. By Jeanne Danemaris. theology and religion: Catholic Evidence Training Outlines. Compiled by Maisie Ward and F. J. Sheed sociology: The Revolt Against Mechanism. By L. P. Jacks. sociology: Money and Social Justice. By the Rev. F. H. Drinkwater. liturgy: Byzantine Architecture and Decoration. By J. R. Hamilton. liturgy: How to Build a Church. By Benedict Williamson. liturgy: Mass for Four Men's Voices. By John Taverner. liturgy: Mass in C Minor (No. 2) for Organ and Four Mixed Voices. By C. H. Kitson. liturgy: Missa Dominicalis for Two Equal Voices with organ accompaniment. By Don Mario Pettorelli. L'Artisan Liturgique. (Quarterly. Abbey of St. André, Lophem, Belgium; 40 Belgian francs annually.) history: Cymru's Oesau Canol gan Yr Athro Robert Richards. (Hughes a'i fab, Wrecsam; 15/-.) history: Winston Churchill and James II. By Malcolm V. Hay. history: The Economic Morals of the Jesuits. By J. Brodrick, S.J. history: Golden Years on the Paraguay. By George O'Neill, S.J. history: Samuel Thomas Wilson, O.P., S.T.M. A Light of the Church in Kentucky. By the Very Rev. V. O'Daniels, O.P., S.T.M. history: L'Europe Tragique. Gonzague de Reynold.